STUDENTS’ PROBLEMS IN WRITING THE TV NEWS TYPESCRIPT - Aryuliva Adnan (Proceedings of ISELT FBS Universitas Negeri Padang, 2016)
Listening as one of language skills learned needs practices inside and outside the classroom. These practices are aimed to provide students with kinds of listening activities which can increase students’ ability in listening skill. Listening to the TV news is one of the weekly assignments given to the students at English Department of Universitas Negeri Padang.  They are asked to listen and watch English News from international news TV stations, such as CNN, BBC, ABC, NHK and Al Jazeera. From this activity students are assigned not only answering the questions WH questions related to the news but also writing the typescript of the news. They are asked to choose the news from any TV stations they like and write the typescript of one headline news, so that the news is not so long.  In doing this assignment, they have to write the typescript of the news as it is. The purpose of asking students to do this assignment is to check whether the students understand or not about the words, the phrases and the sentences read by the news readers. These are related to their knowledge about pronunciation, vocabulary mastery and sentence constructions in listening to the news.